Penerapan Tri Hita Karana di Perpustakaan SMA Negeri 1 Kuta Utara untuk Meningkatkan Literasi Siswa - Ni Nyoman Alit Putri Wardani; Lasmawan I Wayan; Parmiti Desak Putu (SENTRI: Jurnal Riset Ilmiah, 2026)
School libraries are vital facilities in supporting the improvement of students’ reading and writing literacy. In today’s digital era, students’ interest in reading tends to decline as they increasingly access information through social media and gadgets. Moreover, the quality of school libraries has remained below standard over the years, leading to reluctance among the school community to visit and engage in literacy activities there. This study employs a qualitative descriptive case study method, focusing on an in-depth understanding of the processes, interactions, and experiences of students in carrying out literacy activities in the school library. The research subjects include students as library users who benefit directly, teachers as facilitators, and librarians. Data collection was conducted through observation of literacy activities at SMAN 1 Kuta Utara’s library, in-depth interviews with students and teachers, and documentation of literacy programs complemented by library reports. Data analysis involved reducing key information, presenting it in narrative form, and drawing conclusions about the findings related to the application of Tri Hita Karana values in the library of SMAN 1 Kuta Utara to enhance students’ reading and writing literacy. The findings highlight, (1) the application of parhyangan values, by habituating prayer before reading to provide peace of mind, serenity of heart, and the ability to bring forth new knowledge and perspectives in literacy; (2) the application of pawongan values, the creation of harmonious relationships between librarians and users through warm and friendly service that fosters reading interest and enhances literacy; (3) the application of palemahan values, with a representative layout and reading space that is clean, comfortable, cool, and quiet, creating attraction and convenience for users to visit and engage in literacy, while also ensuring librarians feel comfortable in serving users in their work. Based on the guest book data, the average number of daily visits reaches 100 library users who come to read and engage in literacy activities at the library.